Potensi dan Strategi Pengembangan Budidaya Ikan Nila (Oreochromis niloticus) di Kota Kabupaten Puncak Jaya Papua Tengah - Karangan, Agustinus; Cahyono, Indra; Latif, Nursidi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
Since 2016, tilapia fish farming has begun to be developed in Puncak Jaya Regency, especially in several districts in the capital city of the district, including Mulia District, which is the center for developing tilapia fish farming areas. Puncak Jaya Regency is located in a mountainous area with an altitude of 500 - 4000 mbpl with an average of 2237 mbpl above sea level. These geographical conditions are obstacles that must be overcome to develop tilapia fish farming which is highly demanded and needed by the mountain community to meet their daily nutritional needs. This study aims to 1) Analyze the factors and potential of fish farming. 2) fish farming development strategies in the city of Puncak Jaya Regency. The method used was to conduct interviews with questionnaires to business actors in farming, related agencies and officials at the regional government level and the DPRD, then analyzed with IFE and EFE Analysis and to determine the strategy, a SWOT analysis was carried out. The results of the study showed 1) business actors in farming were productive age cultivators with a high school education level (33%), small business scale (40%) and production results of 100 - 250 kg / cycle (46.7%); 2) Internal and external factors that have a great influence are geographical location, government support, fish prices, consumer needs and security which are the main threat factors; 3) Development strategies to increase production by adding cultivation ponds, developing alternative artificial feed with local raw materials, assisting independent seed production and government support to overcome security threats by distributing assistance for cultivation facilities and infrastructure more evenly to all heterogeneous social groups.